EFL Learners’ Perception of ChatGPT Integration in English Learning: Motivation, Skills, and Pedagogical Development - Militansina, Militansina (Journal of Language and Literature Studies, 2025)
This research explores the integration of ChatGPT, a generative AI language model, into English language learning in higher education, emphasizing students’ perspectives on motivation, skill development, and pedagogical integration challenges. Drawing on interpretative qualitative data from semi-structured interviews with seven undergraduate students in Indonesia, the research identifies how ChatGPT enhances students’ autonomy, confidence, and engagement, especially in writing, grammar, and vocabulary development. While students report strong intrinsic motivation and reduced anxiety due to ChatGPT’s non-judgmental interface, they also acknowledge limitations in speaking and listening support. Thematic analysis reveals key themes including emotional responses, perceived usefulness, challenges in trust and overreliance, and expectations for institutional support in pedagogical integration. The findings highlight the importance of lecturer guidance and ethical AI literacy to ensure responsible use. This study contributes by providing empirical evidence on how AI integration can reshape language learning practices, offering clear directions for educators in designing effective instructional strategies and for policymakers in formulating guidelines that balance innovation with responsible use.